Chemical composition of the 2 opposites sides of a deep-sea manganese-nodule from the Peru basin - Nathalie Lemaitre; Jean-Louis Reyss; Vesna Marchig (PANGAEA, 2022)
We discuss the differences in chemical composition between the two opposite sides of a deep-sea manganese nodule. The upper side, facing sea water, contains a hydrogeneous component, whereas the chemical composition of the bottom side is strongly influenced by a diagenetic supply of elements from the underlying sediment.